2018
DOI: 10.1038/s41535-018-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-driven collapse of the relativistic electronic ground state in a honeycomb iridate

Abstract: The electronic ground state in many iridate materials is described by a complex wave-function in which spin and orbital angular momenta are entangled due to relativistic spin-orbit coupling (SOC) [1,2]. Such a localized electronic state carries an effective total angular momentum of J ef f = 1/2 [3,4]. In materials with an edge-sharing octahedral crystal structure, such as the honeycomb iridates Li2IrO3 and Na2IrO3, these J ef f = 1/2 moments are expected to be coupled through a special bonddependent magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 45 publications
(51 reference statements)
8
51
5
Order By: Relevance
“…We first consider α‐Li 2 IrO 3 . The pressure effects in this system has been studied experimentally by X‐ray diffraction measurements with synchrotron radiation and more recently by other X‐ray techniques . These studies reveal that α‐Li 2 IrO 3 undergoes a transition from the monoclinic phase (C2/m space group) to a lower symmetry triclinic phase (Ptrue1¯ space group) at the critical pressure Pc=3.8GPa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first consider α‐Li 2 IrO 3 . The pressure effects in this system has been studied experimentally by X‐ray diffraction measurements with synchrotron radiation and more recently by other X‐ray techniques . These studies reveal that α‐Li 2 IrO 3 undergoes a transition from the monoclinic phase (C2/m space group) to a lower symmetry triclinic phase (Ptrue1¯ space group) at the critical pressure Pc=3.8GPa.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the interplay between electronic correlations ( U ), spin‐orbit coupling (SOC) effects, magnetism and covalent bonding in α‐Li 2 IrO 3 have been explored by DFT simulations and quantum chemistry calculations . Two competing interactions controlling the structural transition at finite pressure are (a) the energy gain due to the local moment formation and (b) the dimerization and the consequent quenching of local moments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments finally showed that the electronic ground state of Na 2 IrO 3 can be well described in terms of a relativistic Mott insulator with a half-filled j eff =1/2-band split by the Hubbard U [17,27,32,33], although it exhibits a significant intrahexagon itinerant character which could lead to a mixing of j eff =1/2 (j 1/2 ) and j eff =3/2 (j 3/2 ) states in the Ir t 2g level [17,34,35]. Compared to Na 2 IrO 3 , for α-Li 2 IrO 3 signs for an increased QMO character was observed at ambient conditions [17] and at low pressures [36].…”
Section: Introductionmentioning
confidence: 96%
“…5d materials are unique for several reasons. First, strong spin-orbit coupling competes with magnetic, crystalfield, many-body Coulomb, and other interactions to drive new physical behaviors [7], such as the J eff = 1/2 state in certain iridates [8,9]. Second, the bonding interactions associated with the larger 5d orbitals promote inter-cation dimerization in pairwise, chain-like, and other complex orderings [10,11].…”
Section: Introductionmentioning
confidence: 99%